2013
DOI: 10.1007/s15010-013-0532-x
|View full text |Cite
|
Sign up to set email alerts
|

Rothia aeria mitral valve endocarditis complicated by multiple mycotic aneurysms: laboratory identification expedited using MALDI-TOF MS

Abstract: Rothia aeria has only rarely been described as a human pathogen. We describe a case of Rothia aeria causing mitral valve endocarditis and multiple mycotic aneurysms, including cerebral mycotic aneurysms. In the case described, early identification of Rothia aeria was achieved using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…Our review of the literature revealed seventeen case reports of non-dental infection caused by R. aeria ( Table 1 ). The most common manifestations of R. aeria infection were endocarditis noted in eight cases [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] and respiratory tract infection noted in four cases [12] , [13] , [14] , [15] . Joint infection [16] , [17] , skin abscess [18] and tubal-ovarian abscess [19] caused by R. aeria were less commonly described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our review of the literature revealed seventeen case reports of non-dental infection caused by R. aeria ( Table 1 ). The most common manifestations of R. aeria infection were endocarditis noted in eight cases [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] and respiratory tract infection noted in four cases [12] , [13] , [14] , [15] . Joint infection [16] , [17] , skin abscess [18] and tubal-ovarian abscess [19] caused by R. aeria were less commonly described.…”
Section: Discussionmentioning
confidence: 99%
“…Joint infection [16] , [17] , skin abscess [18] and tubal-ovarian abscess [19] caused by R. aeria were less commonly described. Only six reported cases were in immunocompetent patients [4] , [5] , [7] , [9] , [10] , [11] , all of which manifested as endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…been reported to date, and m ost were associated with the use of im m unosuppressants for underlying diseases [2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…Only seven cases of R. aeria infection have been reported [2][3][4][5][6][7][8], because most reported Rothia species infection cases were caused by R. dentocariosa and R. mucilaginosa. Both of these are com mon inhabitants of the human oral cavities [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation